Science research writing : for non-native speakers of English - Glasman-Deal, Hilary (Imperial College Press, 2010)
This work is designed to enable non-native English speakers to write science research for publication in English. It is a practical, user-friendly book intended asa fast, do-it-yourself guide for those whose English language proficiency is above intermediate